Is Canakinumab Safe During Pregnancy? New Insights from Three Cases in Slovakia - Branislav Slenker; Katarina Hrubiskova; Lenka Kapustova; Anna Bobcakova; Juraj Ondris; Milos Jesenak (Biologics)
Background and Objectives: Canakinumab, a human recombinant monoclonal antibody against interleukin-1ß (IL-1ß), is indicated for the treatment of selected autoinflammatory periodic fever syndromes and rheumatic diseases. Data on its use during pregnancy remain limited and all are primarily derived from case reports. Although animal studies indicate no evidence of reproductive toxicity, the risk to the fetus or mother remains unknown. This study aims to provide more findings about this important topic. Methods: A retrospective analysis was conducted on three patients followed and treated in the National Center for Periodic Fever Syndromes. Although due to the small sample size, no general conclusions regarding the safety of canakinumab during pregnancy can be drawn. Results: Three maternal-exposed pregnancies were assessed, with no paternal exposure. Diagnoses included mevalonate kinase deficiency, familiar Mediterranean fever and TNF-receptor-associated periodic syndrome. All mothers were treated with canakinumab, and two of those continued the canakinumab treatment during the whole course of pregnancy. The diseases remained under full control during pregnancy, enabling conception in two cases where attempts prior to treatment were unsuccessful. The therapy led to disease control, a reduction in inflammation and subsequently successful conception. One patient underwent IVF repeatedly. All pregnancies resulted in three healthy infants, with no reported miscarriages during the canakinumab-exposed pregnancies, no complications during pregnancies and no serious infections in the newborns. The children had normal development, without any developmental delays or chronic illnesses. Conclusions: The current data, including our findings, indicate no harmful effects of canakinumab during pregnancy. However, because of the scarcity of data, the use of canakinumab during pregnancy should be carefully managed, and women who want to become pregnant should continue treatment only after a thorough benefit–risk evaluation.